1994
DOI: 10.1083/jcb.126.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional interaction of hepatocyte growth factor-scatter factor and its receptor c-met in mammalian brain.

Abstract: Abstract. Hepatocyte growth factor-scatter factor (HGF-SF) is a pleiotropic cytokine with mito-, morpho-, and motogenic effects on a variety of epithelial and endothelial cells. HGF-SF activity is mediated by the c-met protooncogene, a membrane-bound tyrosine kinase. Here, we demonstrate that both genes are expressed in developing and adult mammalian brains. HGF-SF mRNA is localized in neurons, primarily in the hippocampus, the cortex, and the granule cell layer of the cerebellum, and it is also present at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
132
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 43 publications
(48 reference statements)
6
132
0
Order By: Relevance
“…This staining in the somata may reflect an uneven level of c-Met expression among pyramidal cells. These patterns of c-Met ex-pression are mostly consistent with previous reports using a polyclonal antibody (Korhonen et al, 2000) and in situ hybridization (Jung et al, 1994). When the localization was further analyzed in dissociated neurons of the hippocampus, positive signals for c-Met were observed in neurites that were also positive for MAP-2, a marker for neuronal dendrites (Fig.…”
Section: Localization and Tyr-phosphorylation Of C-met In The Hippocasupporting
confidence: 91%
See 1 more Smart Citation
“…This staining in the somata may reflect an uneven level of c-Met expression among pyramidal cells. These patterns of c-Met ex-pression are mostly consistent with previous reports using a polyclonal antibody (Korhonen et al, 2000) and in situ hybridization (Jung et al, 1994). When the localization was further analyzed in dissociated neurons of the hippocampus, positive signals for c-Met were observed in neurites that were also positive for MAP-2, a marker for neuronal dendrites (Fig.…”
Section: Localization and Tyr-phosphorylation Of C-met In The Hippocasupporting
confidence: 91%
“…In situ hybridization (Honda et al, 1995;Jung et al, 1994) and immunohistochemical (Korhonen et al, 2000) studies have indicated that the hippocampus is a prominent site for the expressions of HGF and c-Met in the adult CNS. Here, we confirmed that c-Met protein was localized in hippocampal neurons in adult brain, where it showed a relatively high degree of Tyr-phosphorylation.…”
mentioning
confidence: 99%
“…Although many signals have been identified that modulate dendrite growth and maturation, relatively few have been identified that regulate the initial stages of dendrite elongation [34]. HGF and c-Met are expressed by specific classes of neurons from cerebral cortex, hippocampus, amygdala, and septum as well as by non-neuronal cells [35][36][37]. HGF initiates multiple intracellular signals to regulate protein expression, cytoskeletal rearrangement and motility, and intercellular adhesion in CNS neurons [12,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Sp1, Sp2 and Sp3 which are ubiquitously expressed in various tissues and cell types, Sp4 is known to be brain-speci®c (Kingsley and Winoto, 1991;Fischer et al, 1993;Hagen et al, 1992). Thus Sp4 may activate HGF expression in the central nervous system since the HGF gene is also expressed in this tissue (Jung et al, 1994).…”
Section: Discussionmentioning
confidence: 99%